Unveiling the Magnesium Storage Mechanisms of Co-Sputtered Indium-Tin Alloy Films Using Operando X-ray Diffraction. Issue 1 (6th January 2022) - Cui, Wenrun; Song, Meijia; Jia, Guixing; Wang, Yu; Yang, Wanfeng; Bai, Qingguo; Zhang, Zhonghua
Abstract : Tin (Sn)-based anodes have drawn extensive attention for magnesium ion batteries (MIBs) owing to their low reaction potentials, high theoretical capacities, and compatibility with conventional electrolytes. However, their poor electrochemical reactivity, sluggish kinetics, and large volume changes have obstructed progresses. Additionally, a clear understanding of the Mg storage chemistry is crucial for the development of high-performance MIBs. Here, we prepared self-supporting In-Sn alloy films with different compositions and phase constitutions via a one-step magnetron co-sputtering. As benchmarked with pure Sn film, the single-phase and biphase In-Sn alloy films effectively trigger the alloying reaction of Sn with Mg and further increasing of In significantly improves the electrochemical reactivity of the In-Sn electrodes. More importantly, operando X-ray diffraction was performed to unveil the magnesiation/demagnesiation mechanisms of the In0.2 Sn0.8, In0.2 Sn0.8 /In3 Sn and In3 Sn electrodes, showing that In0.2 Sn0.8 and In3 Sn display different Mg storage mechanisms when existing alone or biphase coexisting. Our findings highlight the significance of the electrode design and mechanism investigations for MIBs.